Karrikinolide Promotes Seed Germination but has no Effect on Leaf Segment Senescence in Triticum aestivum L. - (:unkn) unknown (My University, 2019)
Objective: Germination and senescence are the two most important developmental processes in the plant life cycle. Whileseed germination is an important physiological event for the continuity of species, leaf senescence is also an importantdevelopmental process that impacts crop yields. Karrikins are a group of plant growth regulators found in the smokegenerated by burning plant material. It has been suggested that karrikinolide (KAR1) is generally the most active karrikin interms of stimulating germination.Materials and Methods: In this study, the effect of karrikinolide on germination and leaf segment senescence in wheat wasinvestigated. For this purpose, control, 1 nM, 0.01, 0.1, 1, and 10 μM KAR1 solutions were used. Firstly, the wheat seeds weregerminated in the dark in these solutions and germination percentages and root lengths were measured. Secondly, 4 of firstleaf segments (3cm. each) from 10-day-old wheat seedlings were placed in petri dishes containing 1, 10, 100 μM KAR1 anddistilled water as a control. Following incubation, fresh weight, chlorophyll content, cell death amounts and total proteinamounts were determined.Results: The obtained data shows that 1 μM KAR1 promotes germination and root length to the greatest extent. This suggeststhat karrikins have a promoting effect on the germination of wheat seeds. Our results demonstrate that KAR1 has no effecton leaf segment senescence.Conclusion: Our study suggests that KAR1 has the potential to be used in agriculture to improve germination and seedlinggrowth of crop species.
Keywords: Biyoloji